Traitement d’impact fluide-solide par Ia methode particulaire SPH: Application: ingestion d’oiseau par les turboreacteurs - Bung, Hariddh; Berthillier, Marc; Audic, Stt phane; Combescure, Alain (European Journal of Computational Mechanics, 2000)
A SPH method has been developed for the simulation of soft impacts of a fluid on a structure. The SPH method is coupled to a finite element method using a slave-master contact impact algorithm. An implementation has been peiformed in the Castem-Plexus explicit code. It is applied to bird swalling simulation in a turboreactor engine. The final strains and deformed shapes of the turbine blades are correctly predicted and the computation times are reasonable enough to do industrial applications.